Investigating the influence of language evolution on perception of a continuous meaning space - Swoboda, Kate (The University of Edinburgh, 2010)
There has been a recent resurgence in psycholinguistic experimental studies testing linguistic relativity – the view, associated with Benjamin Lee Whorf (1956), that the language we speak influences our perception and understanding of the environment. Furthermore, recent experimental work in evolutionary linguistics in the Iterated Learning Model applied to humans (e.g., Kirby, Cornish, & Smith, 2008) has proved to be successful at explaining how language transmission can shape its properties. In light of these findings, the research presented here unprecedentedly embarks on testing linguistic relativity from an evolutionary perspective. It is demonstrated that language transmission of two qualitatively different languages evolved in the experiment by Matthews, Kirby, & Cornish (in prep.) – one that promotes the distinction between rotated and unrotated shapes and the other that does not – influences perception of these shapes. This finding suggests that language evolution shapes the conceptual system (semantics) in the speakers’ minds by propagating the ways the world should be perceived and interpreted within a given speech community.
Keywords: language evolution; evolution of semantics; linguistic relativity; continuous meaning space; the Iterated Learning Model; categorisation